2021
DOI: 10.1177/23259671211052519
|View full text |Cite
|
Sign up to set email alerts
|

MRI Findings of Early Osteoarthritis in Patients Who Sustained Septic Arthritis of the Knee After ACL Reconstruction

Abstract: Background: Although a rare complication, septic arthritis (SA) after anterior cruciate ligament (ACL) reconstruction has potentially devastating consequences for the knee joint. Purpose: To prospectively analyze, at a mean 4-year follow-up, subjective, clinical, radiographic, and magnetic resonance imaging (MRI) findings between patients with SA and those with no septic complication after ACL reconstruction. Study Design: Cohort study; Level of evidence, 2. Methods: Of 2006 ACL reconstructions performed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 22 Previous literature showed that the incidence of SA following ACLR ranged from 0.14% to 2.6%. 11 A systematic analysis by Makhni and associates identified 169 infections out of 31,750 patients accounting for 0.53% infection rate. 23 Another extensive review by Gobbi et al, over a 20-year period, reported a total incidence of 0.37% (7 cases out 1850 ACLR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Previous literature showed that the incidence of SA following ACLR ranged from 0.14% to 2.6%. 11 A systematic analysis by Makhni and associates identified 169 infections out of 31,750 patients accounting for 0.53% infection rate. 23 Another extensive review by Gobbi et al, over a 20-year period, reported a total incidence of 0.37% (7 cases out 1850 ACLR).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence ranges from 0.14% to 2.6%. 11 Patients who develop this serious complication generally present with a painful knee joint associated with a restricted range of motion, prolonged joint swelling, local erythema, and fever. 12 An earlier study demonstrated that diabetic patients and those who had received hamstring autografts were more likely to develop postoperative SA.…”
Section: Introductionmentioning
confidence: 99%